In the Market for an ECE Transition-to-school Programme? - Benade, L; De Lautour, N; Stover, S; Stewart, G (Addleton Academic Publishers, 2017)
This article draws on a small evaluation research project, conducted in one early childhood education (ECE) centre in Auckland, New Zealand, with the aim of supporting its capacity for self-review. The centre management and governance team was motivated to seek out the support of research as part of their response to two recent Education Review Office (ERO) reports that had cast doubt over the value of their transition-to-school programme, and the pedagogy used at the centre. This article draws on this evaluation research to discuss knowledge debates that featured in the discourses of the centre and its community: dispute about the value of the transition programme; the paradox of mandatory self-review; and the difficult work of changing practice, in responding to ERO advice to move away from teacher-directed pedagogy.
Keywords: Discourse; Early Childhood Education (ECE); Evaluation research; Pedagogy; Self-review; Transition-to-school